2022
DOI: 10.3389/fmicb.2022.937862
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Profile of S-Layer Proteins Controls Surface Properties of Emetic Bacillus cereus AH187 Strain

Abstract: Many prokaryotes are covered by a two-dimensional array of proteinaceous subunits. This surface layers (S-layer) is incompletely characterized for many microorganisms. Here, we studied Bacillus cereus AH187. A genome analysis identified two genes encoding the S-layer proteins SL2 and EA1, which we experimentally confirmed to encode the two protein components of the S-layer covering the surface of B. cereus. Shotgun proteomics analysis indicated that SL2 is the major component of the B. cereus S-layer at the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…This is especially important in pathogenic bacteria since S-layers play a role in surface adhesion and in interactions with the host's immune system. Furthermore, numerous studies on the in vivo and in vitro morphogenesis of S-layers demonstrated that lattice growth on growing cells is a highly dynamic process 6,7,11,[41][42][43][44][45] . Approximately 500 subunits per second must be synthesized at high growth rates, translocated to the cell surface, and incorporated in a de ned orientation to the existing lattice while maintaining an equilibrium of the lowest free energy 6,44-47 .…”
Section: Discussionmentioning
confidence: 99%
“…This is especially important in pathogenic bacteria since S-layers play a role in surface adhesion and in interactions with the host's immune system. Furthermore, numerous studies on the in vivo and in vitro morphogenesis of S-layers demonstrated that lattice growth on growing cells is a highly dynamic process 6,7,11,[41][42][43][44][45] . Approximately 500 subunits per second must be synthesized at high growth rates, translocated to the cell surface, and incorporated in a de ned orientation to the existing lattice while maintaining an equilibrium of the lowest free energy 6,44-47 .…”
Section: Discussionmentioning
confidence: 99%